Toxicities of docetaxel: original drug versus generics—a comparative study about 81 cases - Elm’hadi, Choukri (Springerplus, 2016)
INTRODUCTION: Docetaxel is a chemotherapy drug widely prescribed in oncology that recognizes a variety of manufactured generics whose toxicity is increasingly reported. The aim of this study was to compare the toxicities between the original and a generics docetaxel in a Moroccan center. METHODS: In a cross sectional study, we enrolled patients treated with docetaxel from the oncology department of the military hospital of Rabat over a period of 2 years (2013–2014). We compared the prevalence of hypersensitivity reactions, febrile neutropenia, peripheral neuropathy, gastrointestinal, cutaneous, and hematologic toxicities, between four different presentations of docetaxel including the original drug. Only grade II or worse adverse events related to chemotherapy were considered. Treatments discontinuations due to toxicity were also compared. Unusual skin toxicities were included. RESULTS: 81 patients were eligible for analysis [43/generics arm vs. 38/original drug arm. Hematological toxicity was significantly more frequent in the generic arm than in the original drug (32.6 vs. 13.2 %; p = 0.04)]. Also, a signifying higher rate of treatment discontinuation was observed in the generic arm (39.5 vs. 7.9 %, p = 0.001). The use of specific generic increase numerically the skin toxicities (17.6 vs. 0 %, p = 0.026). CONCLUSION: Our data suggest that generics of docetaxel are associated with an increase of hematological and cutaneous toxicities, an increase of treatment discontinuation rate and emphasize the need of a regulation of generics’ manufacture.